2017
DOI: 10.1002/ajmg.a.38375
|View full text |Cite
|
Sign up to set email alerts
|

Identification of STAC3 variants in non‐Native American families with overlapping features of Carey–Fineman–Ziter syndrome and Moebius syndrome

Abstract: Horstick et al. (2013) previously reported a homozygous p.Trp284Ser variant in STAC3 as the cause of Native American myopathy (NAM) in 5 Lumbee Native American families with congenital hypotonia and weakness, cleft palate, short stature, ptosis, kyphoscoliosis, talipes deformities, and susceptibility to malignant hyperthermia (MH). Here we present two non-Native American families, who were found to have STAC3 pathogenic variants. The first proband and her affected older sister are from a consanguineous Qatari … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 30 publications
2
33
0
Order By: Relevance
“…One patient with severe presentation (PN5) was compound heterozygous for the recurrent NAM and a novel splice site variant. Similarly, three other reported previously patients with a more severe phenotype carried variants other than the recurrent NAM variant (frameshift or splice site variants; Grzybowski et al, 2017;Telegrafi et al, 2017). However, it is worth noting that a degree of clinical variability is also observed among patients with homozygous NAM variant and among members of the same family, suggesting that factors other than the type of variants could contribute to the phenotypic variability.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…One patient with severe presentation (PN5) was compound heterozygous for the recurrent NAM and a novel splice site variant. Similarly, three other reported previously patients with a more severe phenotype carried variants other than the recurrent NAM variant (frameshift or splice site variants; Grzybowski et al, 2017;Telegrafi et al, 2017). However, it is worth noting that a degree of clinical variability is also observed among patients with homozygous NAM variant and among members of the same family, suggesting that factors other than the type of variants could contribute to the phenotypic variability.…”
Section: Discussionmentioning
confidence: 69%
“…The observation of the NAM variant in various populations often of African descent could point toward a common ancestor of possible African origin. Interestingly, Telegrafi et al (2017) found that the NAM variant was not in linkage with the same haplotype in their two families, implying that these variants originated from unrelated mutational events. Further studies and haplotype analysis might help to further clarify this point.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Distinguishing features of STAC3 -CFZS are short stature and malignant hyperthermia. 7 Whether other clinical features present in our patient are a consequence of MYMK mutations remains to be established through continued follow-up of the known patients 6 and diagnosis and follow-up of new patients with CFZS.…”
Section: Discussionmentioning
confidence: 93%